Contribution To The Study Of The Pre-Cambrian Rocks Of The Harney Peak District Of South Dakota. - Gordon S. Duncan (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1912)
(New York Meeting, February, 1912 THE U. S. Geological Survey, I believe, has almost completed a study of the Harney Peak quadrangle, preliminary to the publication of a report on that, district. As I was engaged for some months on an investigation of the mode of occurrence of the ore-bearing formation in this area, it has seemed to me timely to make public the results of my study, as a contribution to the consideration of this subject. It seems scarcely necessary to describe the locality and general geology of the Black hills of South Dakota, for since 1846 many have contributed information concerning this region, some of the reports bearing such well-known names as those of Walter P. Jenney, Henry Newton, S. F. Emmons, and C. R. Van Hise, while we have only to glance at Bulletin No. 4 of the South Dakota School of Mines, in which Prof. C. C. O'Harra, of that institution, has given us a bibliography of contributions to the geography and geology of the section, to find that other well-known men have studied the district, and have given us the benefit of their researches. The U. S. Geological Survey has made geological maps of nearly the whole of the Black hills, the only quadrangle yet to be completed being, as stated, the Harney Peak district. During the late summer and autnmn of 1910, it was my lot to examine and report. on a considerable area in this neighborhood, which once had been prospected, and in some cases exploited, for tin. This paper gives an account of certain geological phenomena, noted at that time, which greatly influenced my conclnsions. The predominating formation of the district is pre-Cambrian, represented by a highly-cleaved mica-schist, usually very garnetiferous, and sometimes hornblendic. Rising like an island from the surrounding schist is a large mass of granite, known as